The Estimate of Instantaneous Solar Radiation Intensity Using Energy Conversion Method - Gancang Saroja; Lailatin Nuriyah; Chomsin S Widodo; M. F. Novanata (Natural B, Journal of Health and Environmental Sciences, 2018)
The intensity of solar radiation provides information of amount energi that is transferred by the sun in a unit time. The information is used in many sectors for designing and assembling systems with solar energi sources. The measurement of the intensity of solar radiation directly requires a complex set of tools and procedures. This study aims to provide an estimate of instantaneous solar radiation by using energi conversion methods. The working principle of the method used is to capture the flux of solar radiation with a piece of black copper plates and then extract the energi into the water medium through direct contact of the water-copper plates. The increase of fluid temperatur is measured as a function of the time duration of radiation exposure. The radiation intensity value is obtained from derivation of the gradient value of the increasing temperatur. The results show that the energi conversion method gives the radiation intensity value matching the radiation intensity value based on the calculation of astronomical formulation. In the location of the experiment, at noon, the energi conversion method gives an instantaneous solar radiation intensity of 1149, 63 W/m2 with a difference of 0.59% with the calculation result of the astronomical formula.